Necesidad de reformar el art. 71 de La Ley Orgánica de Comunicación, en lo concerniente al papel que deben cumplir los medios y su necesaria regulación de su intervención en el control de la comunicación en el país - Cornejo Tapia, Silvia Marcela (2015)
This research aims to analyze from a legal point of view the situation, regulatory framework and control of the media in the Republic of Ecuador, the nature of the space in which it is developed, ie the radio spectrum and other channels as well as the treatment that our legal system gives. In Ecuador, radio spectrum constitutionally recognized as inalienable, and indefeasible state property necessarily involves the regulation of broadcasting understood as all means, systems or services of radio and television, defined as the first service radio emissions sound, and the second, as the radio service of emissions of images and sounds, both for direct reception by the general public. This research is constituted by a series based on doctrinal and normative standards, as well as comments and real analysis that deepen the treatment that should be given to radio and television in the country. Thus, the understanding of this complex subject, which in sufficiently objective opinions, is known and dominated by people who have direct relation relationship, but it should be widely known by all, is presented and in turn analyzed taking into account technical and legal regulations force as well as the most notorious cases this activity has sparked interest among citizens. Processes and requirements for the granting of radio and television frequencies are described according to the provisions of the Communications Law, Law on Radio and Television, its General Regulations and other resolutions issued by the regulatory body of the sector, the former National Council for Radio and Television CONARTEL and current National Telecommunications CONATEL, Telecommunication authority to this date.Concepts and basics of technical terms basic to analyze the field of radio and television, structure and importance of radio spectrum as a means through which these media works are cited. It refers to the process of termination of a concession, causal and express processed by the Act and the Regulations, which in the case of expiry of this, the possibility and budgets for the renewal thereof is analyzed, including. Also any infringements that may arise for dealers, both technical and administrative, appropriate sanctions and consequences for repeat offenses described in its perpetration. Finally, other criteria are discussed, the main practical problems that traverse stations and its dealers, situations that were cited and observed by the Comptroller General and other entities audited and investigated these events